Doping-free white organic light-emitting diodes without blue molecular emitter: An unexplored approach to achieve high performance via exciplex emission - Luo, Dongxiang (2017)
Doping-free white organic light-emitting diodes (DF-WOLEDs) are promising for the low-cost commercialization because of their simplified device structures. However, DF-WOLEDs reported thus far in the literature are based on the use of blue single molecular emitters, whose processing can represent a crucial point in device manufacture. Herein, DF-WOLEDs without the blue single molecular emitter have been demonstrated by managing a blue exciplex system. For the single-molecular-emitter (orange or yellow emitter) DF-WOLEDs, (i) a color rendering index (CRI) of 81 at 1000 cd|m2 can be obtained, which is one of the highest for the single-molecular-emitter WOLEDs, or (ii) a high efficiency of 35.4 lm|W can be yielded. For the dual-molecular-emitter (yellow|red emitters) DF-WOLED, a high CRI of 85 and low correlated color temperature of 2376 K at 1000 cdm2 have been simultaneously achieved, which has not been reported by previous DF-WOLEDs. Such presented findings may unlock an alternative avenue to the simplified but high-performance WOLEDs.